Peningkatan Sikap Ilmiah Siswa melalui Model Inkuiri Terbimbing pada Materi FPB dan KPK Kelas IV di Sekolah Dasar Negeri 34 Pontianak Selatan - Maryani, Utami Sulis; Bistari, Bistari; Halidjah, Siti; Kartono, Kartono; Pranata, Rio (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2023)
Through guided inquiry models of least common multiple (LCM) and greatest sommon divisior (GCD) class IV materials, the general goal of this study is to describe the rise in students' scientific attitudes at SD Negeri 34 Pontianak Selatan. Using classroom action research (CAR), this study was conducted over two cycles with planning, action, observation, and reflection phases. Study the subject. The subjects of this research were 30 students of class IVB at SDN 34 Pontianak Selatan. The purpose of this research is to increase students' scientific attitudes through the application of guided inquiry learning models. The scientific attitudes tested in this study were adapted from Gega which consist of the aspects of curiosity, critical thinking, invention, and fortitude. In cycle I, the result of curiosity during the results of meetings 1 and 2 revealed values of 77.50% and 80%, respectively, and in cycle II, the results of meetings 1 and 2 revealed values of 83.33% and 87.50%. In cycle I, meeting 1 and meeting 2 showed values of 80% and 85% for critical thinking attitudes, while in cycle II, meeting 1 and meeting 2 show values of 90% and 93.33%. The values for students' discovery attitudes in cycles I and II of meetings 1 and 2 are 65% and 75%, respectively, while the values for cycle I of meetings 1 and 2 are 76.66% and 83.33%. The last one is firm attitude in cycle I of meetings 1 and 2 shows the values ​​of 71.66% and 76.66%, and in cycle II meetings 1 and 2 obtained values ​​of 85% and 90%. Based on the research results, we can conclude that SD Negeri 34 Pontianak Selatan has increased the use of the guided inquiry learning model for class IV least common multiple (LCM) and greatest common divisior (GCD) materials from cycle I to cycle II.